Обґрунтування показників ефективності системи забезпечення установи cпеціальними картами та фотодокументами про місцевість - Савчук, Р. (Видавництво Львівської політехніки, 2016)
Проаналізовано функціонування системи забезпечення спеціальними картами і фотодокументами про місцевість провідних країн світу, основні завдання топогеодезичного забезпечення установи і вимоги до топогеодезичного забезпечення. Визначено й обґрунтовано показники ефективності системи забезпечення установи спеціальними картами і фотодокументами про місцевість. Проанализировано функционирование системы обеспечения специальными картами и фотодокументами о местности ведущих стран мира, основные задачи топогеодезического обеспечения учреждения и требования к топогеодезическому обеспечению. Определены и обоснованы показатели эффективности системы обеспечения учреждения специальными картами и фотодокументами о местности. The need for constant and agencies in identifying and obtaining subjective topogeodesic data for better planning and operations, increasing demands for speed, accuracy and reliability of information topo-geodetic definition that due to high dynamics of modern operations, the development of precision strike systems and systems change their tactical and technical characteristics and increased capacity, the introduction of automated control systems need to respond quickly to changing circumstances determine the need to improve the existing system of special maps and photographs of the area agencies. The article analyzes the functioning of the system of special maps and photographs of the area leading countries, the main tasks of Surveying software requirements for institutions and Surveying software. Defined and reasonable performance system of institutions with special maps and photographs of the area.
Обоснование показателей эффективности системы обеспечения учреждения специальными картами и фотодокументами о местности
Rationale for indicators effectiveness of the institution specially maps аnd photographs of the area
Keywords: топогеодезичне забезпечення; спеціальні карти та фотодокументи про місцевість; ефективність; точність; надійність